How well do you know your alumni? A word on alumni segmentation - Baraga, Barbara (ICAReAlumni Conference Proceedings, 2019)
When talking about knowing our alumni, we tend to talk about activities, figures, statistics and aims. However, in order to reach out to them we need to start talking about who they really are. What they want and need, how they live their lives, what excites them, what they dislike, where can we find them in order for our messages to reach them? The biggest challenge we face in alumni relations is the sheer number of target groups we’re addressing. It’s a huge audience. We’re addressing everyone from baby boomers to generations X and Y, millennials and Gen Zs. And not only that. We’re also addressing university management and other decision makers, our co-workers, students and business partners. How to reach out to any of them, what tools to use, how to motivate them, how to know them better in order to interact with them more successfully? In order for our everyday work to get momentum? Detailed segmentation and specific communication tools for each target group are the answer. By using methods like empathy map, surveys and interviews, we can evaluate what our alumni and stakeholders are expecting to get from us. Knowing about them and their interests not only helps us be more efficient at what we do but also helps us invest in activities that bring our alumni and other stakeholders the most benefit. If we want to reach all of our alumni, we need to address them in different ways, with different communication tools and different contents, different actions need to be taken and different events need to be organized. If we fail at segmentation, we eventually face consequences like: our activities are meaningless to our audience resulting in low event attendance, our messages don’t get across, our brand is unrecognised within our target groups, our alumni and stakeholders show little interest in what we do etc. Knowing your partner well is vital for any successful long-term relationship. Therefore, segmentation is a crucial part in alumni relations and it needs to be done early on in development process. It also needs to be periodically repeated. There is no other way of knowing what our alumni want and need if we do not invest time in getting to know their interests. And if we don’t know them, how can we succeed in building meaningful relationships with them?